Validation Of A Nomological Network Of Use-Diffusion - LEEN, JASMINE YEAP AI (2005)
In particular, a series of causal relationships were conceptualized to represent a nomological network to model use diffusion process from initial usage of the internet to its impact on future consumption. It was discovered that the model-implied (use-diffusion model) covariance matrix was found to closely fit the sample population dataset. This shows that a parsimonious model that fully represents the use-diffusion process was successful.